The philosophy of media from the language of forms and the representational nature of the subject in the work of Leroi-Gourhan and the phenomenology of language of M. Merleau-Ponty to a phenomenology of the non-whole - Mitrou, Yiannis (Dia-noesis: A Journal of Philosophy, 2025)
This article investigates the philosophical foundations of media by re-examining the concepts of form, representation, and embodiment through a phenomenological lens. It begins with André Leroi-Gourhan’s notion of the language of forms, emphasizing how technical gestures and symbolic expression evolve together and showing how the externalization of thought into material supports lays the groundwork for the mediation between body and world. This archaeological perspective is then brought into conversation with Maurice Merleau-Ponty’s phenomenology of language, in which expression is understood not simply as a vehicle for representation but as the very process through which meaning emerges within lived, perceptual experience. By tracing the dialogue and tension between these two approaches, the article introduces a phenomenology of mediation—an approach that examines how meaning arises through the interplay between embodied perception and media forms, rather than through fixed representations. Both thinkers, though distinct in their frameworks, point toward a redefinition of mediation that unsettles the traditional subject-object dichotomy by highlighting the dynamic relationship between bodily activity and symbolic systems. Expanding on these foundations, the article advances the concept of a Phenomenology of the non-whole. This perspective understands media not as totalizing or closed systems of representation, but as open-ended, fragmentary processes that express the inherent incompleteness and relational nature of human experience; in other words, it explores how media articulate the partial, pre-representational structures through which sense is made. By clarifying these concepts, the discussion becomes accessible to readers from diverse backgrounds, fostering deeper engagement with the core arguments.